A cross-sectional study to assess the cardiovascular risk of chronic cannabis smoking through electrocardiograph (ECG): ECG changes among cannabis, tobacco & non-smokers. (2021) - Shukla, Pawan Kumar; Sharma, Rishi; Meshram, Raviprakash; Das, Anindya; Bastia, Binaya Kumar
Highlights: All the cannabis smokers reported to us were males. Cannabis smokers were younger (26.44 years) compared to tobacco smokers (31.22 years) and non-smokers (31.34 years). The QRS-complex duration was shortened in cannabis smokers compared to tobacco smokers ( p = 0.007). The cannabis group did not show significant differences for ST-segment duration in comparison with the other groups. However, ST-segment duration was shortened among tobacco smokers compared to non-smokers ( p = 0.044). Abstract: Background: Cannabis is one of the most consumed illicit drugs in India. Long term effects of cannabis smoking on the cardiovascular system are still not fully known. The present study explores cardiovascular abnormalities in asymptomatic cannabis smokers by comparing their electrocardiogram (ECG) with tobacco smokers and non-smokers. Methods: The study included 50 participants in each of the three groups: cannabis, tobacco and non-smokers, between the age group 18–40 years. ECG was recorded and the following parameters were compared: Age, Heart rate, RR-interval, P-wave, PR-interval, QRS-complex, QT-interval, QTc-interval, ST-segment and T-wave duration. Results: The mean age of cannabis smokers, tobacco smokers, and non-smokers were 26.44, 31.22 and 31.34, respectively. Cannabis smokers were younger than tobacco smokers and non-smokers. All the participants reported to us were males. The QRS complex duration was shortened in cannabis smokers compared to tobacco smokers. The ST-segment duration was shorter among tobacco smokers compared to non-smokers. Conclusions: The study proposes cannabis as a potential risk factor for adverse cardiac events as an acute and chronic effect. Clinicians could also use our findings to correlate cardiac complaints of a cannabis dependent patient. ECG could be a quick and affordable modality for investigating such patients. The subjects of the cannabis group had younger age than subjects of the other groups.